The golden hour - Moss, Todd (G.P. Putnam's Sons, 2014)
Stymied by infighting and turf battles after being appointed director of the new State Department Crisis Reaction unit, Judd Ryker attempts to prove himself during a coup in Mali that becomes a violent maelstrom of dominating personalities and shifting loyalties.